Source Finding in the Era of the SKA (Precursors): Aegean 2.0 - Hancock, P.; Trott, Cathryn; Hurley-Walker, Natasha (Cambridge University Press, 2018)
In the era of the SKA precursors, telescopes are producing deeper, larger images of the sky on increasingly small time-scales. The greater size and volume of images place an increased demand on the software that we use to create catalogues, and so our source finding algorithms need to evolve accordingly. In this paper, we discuss some of the logistical and technical challenges that result from the increased size and volume of images that are to be analysed, and demonstrate how the Aegean source finding package has evolved to address these challenges. In particular, we address the issues of source finding on spatially correlated data, and on images in which the background, noise, and point spread function vary across the sky. We also introduce the concept of forced or prioritised fitting.